2021
DOI: 10.1111/mcn.13191
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a baby‐friendly workplace support intervention on exclusive breastfeeding in Kenya

Abstract: Exclusive breastfeeding (EBF) during the first 6 months of life is crucial for optimizing child growth, development and survival, as well as the mother's wellbeing. Mother's employment may hinder optimal breastfeeding, especially in the first 6 months. We assessed the effectiveness of a baby-friendly workplace support intervention on EBF in Kenya. This pre-post intervention study was conducted between 2016 and 2018 on an agricultural farm in Kericho County. The intervention targeted pregnant/ breastfeeding wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 34 publications
0
14
0
1
Order By: Relevance
“…The most frequently reported infant feeding measure was EBF. Most studies [ 17 , 19 , 28 , 30 , [32] , [33] , [34] , [35] , [68] , [149] ] defined EBF on the basis of 24-h recall (24 h preceding the interviews) using the WHO/UNICEF definitions (WHO, 2021). Studies measured the prevalence of EBF at a range of time points, from 1 to 6 mo.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequently reported infant feeding measure was EBF. Most studies [ 17 , 19 , 28 , 30 , [32] , [33] , [34] , [35] , [68] , [149] ] defined EBF on the basis of 24-h recall (24 h preceding the interviews) using the WHO/UNICEF definitions (WHO, 2021). Studies measured the prevalence of EBF at a range of time points, from 1 to 6 mo.…”
Section: Resultsmentioning
confidence: 99%
“…Only 1 study reported results from a workplace intervention [ 33 ]. This intervention, conducted among tea farm workers in Kenya, tested exposure to a Baby-Friendly Workplace Initiative that included onsite or community-based daycares, lactation rooms, breastmilk pumps, access to refrigeration, and mother and infant-friendly work policies.…”
Section: Resultsmentioning
confidence: 99%
“…Excessive workload, caesarean section delivery, discouragement and criticism inadequate creche facilities at the workplace, inadequate caregivers at home, inadequate knowledge about expressed milk are barriers to EBF for employed mothers [ 44 , 45 ]. Evidence suggested a baby-friendly workplace for employed mothers was effective for improving EBF practices [ 46 , 47 ]. Also, better knowledge, education, counselling, home support, six-months maternity leave, and flexibility at work are the enablers of exclusive breastfeeding for employed mothers in LMICs [ 44 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The national framework in Kenya included key enablers such as: capacity building, mentorship, integration, social mobilsation and supervision [6]. Integration was also highlighted as critical for Kenya [106,107]. The community basis of Step 10 of the BFHI itself was seen to be critical for sustained improvements [10] and a lack of community services was seen to be a barrier to improvements [71].…”
Section: Pattern 4: the Baby Friendly Community Initiative (Step 10)mentioning
confidence: 99%